Role of crystallization water molecules on hydrogen-bonded structures and dielectric phase transitions in amino trimethylene phosphonic acid-based crystals. (30th May 2017) - Sun, Yu-Ling; Zheng, Bei-Bei; Zhang, Wen
Abstract : Amino trimethylene phosphonic acid-based organic salts show crystallization water molecule-triggered dielectric transitions and relaxations. Abstract : Three hydrogen-bonded organic salts (HTBA)2 (H4 ATMP)·(H2 O)3 (1 ), (HTBA)6 (H3 O)(H2.5 ATMP)2 ·(H2 O)2 (2 ) and (HTBA)6 (H3 ATMP)2 ·H2 O (3 ) were synthesized by combining different molar ratios of amino trimethylene phosphonic acid (H6 ATMP) and tert -butylamine (TBA). There are three-dimensional hydrogen-bonded networks in1–3 . The crystallization water molecules that are loosely trapped in the supramolecular hydrogen-bonded networks in1 and2 undergo order–disorder transitions whose dynamic changes are likely to be responsible for dielectric transitions and relaxations.